Tissue transglutaminase autoantibodies in children with newly diagnosed type 1 diabetes are related to human leukocyte antigen but not to islet autoantibodies: A Swedish nationwide prospective population-based cohort study - Mara Cerqueiro Bybrant; Lena Grahnquist; Eva Örtqvist; Cecilia Andersson; Gun Forsander; Helena Elding Larsson; Åke Lernmark; Johnny Ludvigsson; Claude Marcus; Annelie Carlsson; Sten A Ivarsson (Taylor & Francis Group, 2018)
Objectives: This study explored the association between tissue transglutaminase autoantibody (tTGA), high-risk human leucocyte antigen (HLA) genotypes and islet autoantibodies in children with newly diagnosed type 1 diabetes (T1D). Patients and methods: Dried blood spots and serum samples were taken at diagnosis from children <18 years of age participating in Better Diabetes Diagnosis (BDD), a Swedish nationwide prospective cohort study of children newly diagnosed with T1D. We analyzed tTGA, high-risk HLA DQ2 and DQ8 (DQX is neither DQ2 nor DQ8) and islet auto-antibodies (GADA, IA-2A, IAA, and three variants of Zinc transporter; ZnT8W, ZnT8R, and ZnT8QA). Results: Out of 2705 children diagnosed with T1D, 85 (3.1%) had positive tTGA and 63 (2.3%) had borderline values. The prevalence of tTGA was higher in children with the HLA genotypes DQ2/2, DQ2/X or DQ2/8 compared to those with DQ8/8 or DQ8/X (p = .00001) and those with DQX/X (p ≤ .00001). No significant differences were found in relation to islet autoantibodies or age at diagnosis, but the presence of tTGA was more common in girls than in boys (p = .018). Conclusion: tTGA at T1D diagnosis (both positive and borderline values 5.4%) was higher in girls and in children homozygous for DQ2/2, followed by children heterozygous for DQ2. Only children with DQ2 and/or DQ8 had tTGA. HLA typing at the diagnosis of T1D can help to identify those without risk for CD.